Analisis Sistem Informasi Akuntansi Piutang Dan Sistem Pengendalian Internal Piutang Pada Perusahaan Kontruksi Di Surabaya: Studi kasus PT.Sarana Remaja Mandiri - Siti Mudzalifah; Agus Subandoro (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
PT Sarana Remaja Mandiri is a construction company spread throughout Indonesia to handle customers at PT Sarana Remaja Mandiri to improve company services for profit. Customers can cooperate with PT Sarana Remaja Mandiri through credit payments so that credit transactions occur. Credit transactions carry the risk of bad debts and the age of receivables. The author aims to analyse the accounting information system and accounts receivable internal control system at PT Sarana Remaja Mandiri. The analytical method used is descriptive qualitative. The population and sample in this study were PT Sarana Remaja Mandiri and used receivables data. The results obtained on the accounts receivable accounting information system at PT Sarana Remaja Mandiri still use a manual system with Microsoft Excel, which is less accurate. Furthermore, based on the internal control system (COSO framework), receivables at PT Sarana Remaja Mandiri are still not optimal and effective in terms of procedures, monitoring, information and communication